DEVELOPMENT OF STEM-PjBL INTEGRATED PHYSICS MODULE (Science, Technology, Engineering, and Mathematics – Project Based Learning) IN DIRECT CURRENT ELECTRICITY MATERIALS TO IMPROVE LEARNING OUTCOMES - Widiawati, Reni; Virman, Virman; Siallagan, Johnson (Jurnal Ilmu Pendidikan Indonesia, 2022)
This research is a research and development (research & development) which aims to find out how to make an integrated physics module STEM-PjBL, how to develop an integrated physics module STEM-PjBL, the feasibility of an integrated physics module STEM-PjBL, and learning outcomes using the integrated physics module STEM-PjBL on direct current electrical materials and the advantages and disadvantages of the STEM-PjBL integrated physics module.The results of the study show that there is an increase in student learning outcomes after using the STEM-PjBL integrated physics module, based on the average n-Gain result of 0.66 in the medium category which means that the use of the STEM-PjBL integrated physics module is good in improving student learning outcomes